Association between nutritional and psychosocial factors and physical activity levels among working women - Khusani, Siti Affira (2012)
Many studies have shown that physical activity along with a healthy diet are major components in the prevention of chronic diseases. A cross-sectional study was conducted among 215 working women aged between 18 to 55 years from four private corporate listed companies in Petaling Jaya to determine factors related to their physical activity levels. A self-administered questionnaire which include socio-economic profile, the International Physical Activity Questionnaire (IPAQ), 2-day 24 hour dietary recall, psychosocial factors which determined perceived barriers and benefits to physical activity, self efficacy to physical activity and an 8-item questionnaire on current behavioural stage of physical activity were used to obtain information for this study. A majority of the respondents were Malays (81.9%),followed by Chinese (10.2%) and Indians (7.9%) and their mean age was 30.14 ± 7.59 years. Most were executives (63.3%), while the remaining respondents were non-executives (25.6%) and managers (11.2%). The mean weight, height, body mass index (BMI) and waist circumference were 59.4±13.1 kg, 1.6±0.6 m, 23.7±4.8 kg/m² and 77.0±12.1cm respectively. There were 24.7% and 7.9% who were overweight and obese respectively while 34% were at risk of abdominal obesity. About 28.8% of the respondents were in the low physical activity level category, whereas 48.8% were in the moderate and 22.3% were in the high physical activity categories. The respondents’ average energy intake was 1404.7±346.7kcal/day. For socio-demographic factors, only income showed an association with physical activity level while no correlations were found between nutritional factors and physical activity level. For psychosocial factors, perceived barriers to physical activity (r= 0.222, p<0.05) and perceived benefits to physical activity (r=0.227, p<0.05) were positively correlated with physical activity. However, physical activity was not correlated with self-efficacy to physical activity. In addition, respondents who are active based on their current behavioural stage of physical activity were in the high physical activity category (χ2 = 51.923; p < 0.05) and those with middle income were in the high physical activity category (χ2= 11.017; p < 0.05). Data obtained were analyzed by using SPSS for Windows version 13. Multivariate analysis for contributors of physical activity showed that current behavioural stage of physical activity (contemplation and preparation stages) and perceived benefits to physical activity were found to be significant in explaining physical activity among working women. The R-squared (Coefficient of Determination) of 0.165 implied that three predictor variables (contemplation stage, preparation stage and perceived benefits to physical activity) explained about 16.5% of the variation in physical activity (R2 = 0.165, F (204, 3) = 13.766; p = 0.0001). Further studies are essential to confirm these finding among the general working women population. Attempts to design health promotion programs on physical activity for these women should take into consideration and incorporate the factors identified.